Internalization of Pancasila Values and Nationalism in High Schools Through Citizenship Education - Arifin Arifin (AL-ISHLAH: Jurnal Pendidikan, 2021)
As citizens and the future generation, high school students are required to understand and carry out their rights and obligations according to their age level. Citizenship Education as a subject in schools must emphasize building their character. The substance of learning begins to make citizens who can participate effectively, intelligently, democratically, and responsibly. This literature study scrutinized this education pattern by analyzing six articles published in different settings in Indonesian high schools. The study results explain that Citizenship Education is directed to achieve two balanced main goals. First, Citizenship Education is functioned to improve students’ knowledge and skills about ethics, morals, and principles in the life of the nation and state, then to shape attitudes, behaviour, and personality by the noble values of the Indonesian nation. These two goals should be achieved so that students understand scientific concepts and principles and can do something using scientific concepts and principles that they have mastered in everyday life. Citizenship education should equip students with adequate intellectual knowledge and skills, which allow them to participate intelligently and responsibly in various dimensions of life to form democratic attitudes.